SMART GOVERNANCE MELALUI SISTEM INFORMASI ADMINISTRASI SURAT APLIKASI “SIPADEK” DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA JAMBI - Shully Mumpuni Anjani Putri; Eem Nurnawati; R. Nina Karina (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
SIPADEK (Office Administration Service Information System) is an application for office correspondence administration services that has some features of digital mail disposition, incoming and outgoing email, letter, mail search, digitallogue and striverailature, and archival letter, the schedule event of the meeting. This research is a study to see how far the implementation of the Electronic Mail Information System (SIPADEK) in the Public Works and Spatial Planning Office of Jambi City leading to Smart Governance. The results make it clear that through the application SIPADEK get useful implementation in helping to improve the effectiveness of correspondences in Public Works and Spatial Planning Office of Jambi City. This app streamlines the process of capturing, searching, and disseminating mail digitally, thereby decreasing dependence on manual procedures and paper usage. This research also identified some barriers, including end user application competency (which is often not there), poor staff motivation, under-provisioned data networks and upload capacities. To overcome these obstacles, it is recommended to provide assistance and training, periodic evaluation and monitoring dashboards, data security and protection, as well as support from local authorities and management. In conclusion, the implementation of the application SIPADEK at the Public Works and Spatial Planning Office of Jambi City shows great potential in supporting smart governance, although it still requires some improvements and enhancements for the optimal utilization of this application. Keywords: Smart Governance, SIPADEK, 3 dimensions, human, organization, technology.